GENERATIONAL CLASSIFIER OF MODERN RUSSIAN SOCIETY - A. V. Milekhin; A. V. Sidorina (Вестник университета)
The purpose of the work is to carry out the segmentation of modern Russian society by generational groups, based on the theory of modern generational segmentation. Segmentation is the first necessary step in the analysis of each generational group in terms of lifestyle and value picture of the world. In accordance with the Russian cultural and historical development the authors identified 6 generations, whose representatives live in modern Russian society: “revolutionary generation”, “military generation”, “thaw generation”, “stagnation generation” (generation X), “fracture generation” (generation Y), “digital generation” (generation Z). The article also reveals the essence of the category “generation” from the point of view of sociology.